INCLUSION IN HIGHER EDUCATION THROUGH THE (INTER)CULTURAL VALUES AND PRACTICES OF STUDENTS STUDY OF REPRESENTATIONS IN FRANCE AND ARMENIA - Basco , L.; Derhy Kurtz , B.W. L. (Modern Psychology, 2021)
The article presents the results of a comparative study inclusion in higher education through the (inter) cultural values and practices of students from France and Armenia. The problem of inclusion in higher education is always relevant, as it is necessary to understand how this is possible so that all students can fully participate in their studies and, thus, succeed at the university. In the course of a long-term interview with students of the two countries, questions were formulated that are related to the subjects studied, to university education and the atmosphere, the development of the student’s personality, his communications with teachers and other students, and others like that. One of the conclusions is that students who exchange activities, (inter) cultural practices with other students, gradually become participants in building the specific community that is being created.